About epew and foikes: An ethnobotanical and ethnohistorical analysis of plants among Mapuche and Rankulche people (Quinto Sol, 2018)
In order to understand the value and appropriation of plants by the societies that inhabit and inhabited the centre of the present Argentine Republic, a transdisciplinary approach is proposed where the interests of Archaeology, Ethnobotany and Ethnography converge. Myths, legendsand stories compiled from an extensive bibliographic research on direct oral sources published and reinterpretations made by different authors on these same sources were analyzed. The bibliographic compilation included the South of La Pampa province, the Humid Pampa sub-region, North of Patagonia, and to the West, the Andean zone and south-central Chile (Wall-Mapu and Mamül-Mapu). The data obtained are analyzed in relation to space-temporal variables, the context of utilization-appropriation and the vernacular denomination of the plants. Archaeological research on the use of plants and their importance to the hunter-gatherers of La Pampa during the latter part of the Holocene is conceived as a way of rescuing this traditional way of life. They become an important root for the construction of the identity of the Pampean peoples today.
Keywords: traditional botanical knowledge; transdisciplinar; stories; Pampa and Northpatagonia